Outcome assessment of patients classified through the Manchester Triage System in emergency units in Brazil and Portugal - Helisamara Mota Guedes; Francielli Aparecida Araújo; Domingos Pinto Júnior; José Carlos Amado Martins; Tânia Couto Machado Chianca (Universidad de Antioquia, 2017)
Introduction. The aim was to evaluate the outcomes of patients' treatment classified according to the Manchester Triage System (MTS) in two large hospitals. Methods. Historical cohort study performed in two hospitals in different countries: one emergency unit of a hospital in Portugal, and another in Brazil.The studied population was composed of all patients attended and triaged by nurses in emergency services using the MTS, based on data obtained through the ALERT software. The sample in this study was composed of 158 959 triages in Portugal and 155 121 in Brazil. Results. The higher the priority attributed to the patient according to the MTS, the longer the hospital stay and risk of death. For both groups, the higher therisk classification of the patient, the greater the risk of death when compared to the group classified as "green". In Portugal, patients classified in the "red"category according to the MTS had 1 516-fold higher risk of death compared to those classified in the green category, and in Brazil, this risk was 1 177-fold higher. Conclusion. In both countries, the MTS proved to be a good predictor of length of hospital stay and death.  How to cite this article: Guedes HM, Araújo FA, Júnior DP, Martins JCA, Chianca TCM. Outcome assessment of patients classified through the Manchester Triage System in emergency units in Brazil and Portugal. Invest. Educ. Enferm. 2017; 35(2):174-181.